ANALISIS FAKTOR PENYEBAB KEMISKINAN DI KABUPATEN KERINCI DARI DIMENSI KULTURAL - Ahmad Hafizd; Ali Anis; Mike Triani (Jurnal Ecogen, 2018)
This research have the aim to knowing the influence of several kind  about gender head of family, dependents of family, the floor educational head of family, essence life head of family, essence art head of family, essence time for head of family, essence relation with the nature head of family, essence relation with others head of family, the tribe head of family, the status identity head of family and the gender, dependents of family, the floor of education, the essence life, the essence art, the essence time, the essence relation with nature, the essence relation with human about the poperty floor in regency of  Kerinci with using regrecy logistic analyse method. The result of regecy logistic showing that variable of floor in educational, the several dependents, essence relation with the nature have the influence that significant about the poverty in regency of Kerinci. While the kind of variable gender, essence life, essence art, essence time, essence with other, the tribe and status demography not significantly to influential about the variety in regency of Kerinci. Keyword :  Poverty level, gender, defendens of family, dependents of education, essence life, essence art, essence time, relation essence with nature, relation essence with human.